2012
DOI: 10.1007/978-3-642-25878-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Partially Drawn Links for Directed Graph Edges

Abstract: We investigate the readability of node-link diagrams for directed graphs when using partially drawn links instead of showing each link explicitly in its full length. Providing the complete link information between related nodes in a graph can lead to visual clutter caused by many edge crossings. To reduce visual clutter, we draw only partial links. Then, the question arises if such diagrams are still readable, understandable, and interpretable. As a step toward answering this question, we conducted a controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…An important concept to capture the difficulties users face is cognitive load [WPCM02,HEH09]. A range of works [BVKW11,HIvWF11] are trying to mitigate this problem and present their superiority over baseline methods in controlled user experiments. A range of other challenges, including crossrepresentation comparisons, arises when studying representations of graphs that change over time [AP16].…”
Section: Summary Of Approachesmentioning
confidence: 99%
“…An important concept to capture the difficulties users face is cognitive load [WPCM02,HEH09]. A range of works [BVKW11,HIvWF11] are trying to mitigate this problem and present their superiority over baseline methods in controlled user experiments. A range of other challenges, including crossrepresentation comparisons, arises when studying representations of graphs that change over time [AP16].…”
Section: Summary Of Approachesmentioning
confidence: 99%
“…Burch et al [6] investigated in their study the readability of directed graphs shown with partially drawn links instead of links of full length. This approach reduces link intersections and can lead to shorter task completion times but at the cost of higher error rates.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, classical straightline node-link drawings thereof quickly become ineffective for most, if not all, tasks they address. This is often referred to as the edge congestion [CR01, WCG03, LKS * 11], visual clutter [ED07, BVKW11,NEH13], or hairball problem [SH13]. Bundling is one class of methods that aims to alleviate this problem, along graph clustering and interaction, as further outlined in Sec.…”
Section: Definitionsmentioning
confidence: 99%